2019
DOI: 10.1103/physrevb.99.094202
|View full text |Cite
|
Sign up to set email alerts
|

Universality of eigenchannel structures in dimensional crossover

Abstract: The propagation of waves through transmission eigenchannels in complex media is emerging as a new frontier of condensed matter and wave physics. A crucial step towards constructing a complete theory of eigenchannels is to demonstrate their spatial structure in any dimension and their wavecoherence nature. Here, we show a surprising result in this direction. Specifically, we find that as the width of diffusive samples increases transforming from quasi one-dimensional (1D) to twodimensional (2D) geometry, notwit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…These channels are useful in imaging and communication [5,10] and are an important building block of quantum transport theory in scattering samples [11][12][13][14][15]. The predicted theoretical distribution of the singular values in a multiple scattering waveguide is a bimodal distribution known as the Dorokhov-Mello-Pereyra-Kumar curve [16,17] and the properties of transmission channels are a subject of recent intense research [7,10,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In an open optical system, the finite field of view and finite numerical aperture of the optics and the escape of energy parallel to the surface of the sample make it impossible to measure the complete matrix.…”
Section: Introductionmentioning
confidence: 99%
“…These channels are useful in imaging and communication [5,10] and are an important building block of quantum transport theory in scattering samples [11][12][13][14][15]. The predicted theoretical distribution of the singular values in a multiple scattering waveguide is a bimodal distribution known as the Dorokhov-Mello-Pereyra-Kumar curve [16,17] and the properties of transmission channels are a subject of recent intense research [7,10,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In an open optical system, the finite field of view and finite numerical aperture of the optics and the escape of energy parallel to the surface of the sample make it impossible to measure the complete matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Since the wave equation obtained from the Dirac equation is of a substantially different type from the Schrödinger equation and the electromagnetic wave equation, we expect conceptually new localization phenomena to arise in Dirac materials. Anderson localization in pseudospin-1/2 systems in a random one-dimensional (1D) scalar potential has been studied theoretically by several authors [38][39][40][41][42][43]. It has been shown that localization is destroyed at normal incidence due to the Klein tunneling effect.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson localization of pseudospin-1 Dirac particles in a random 1D scalar potential was studied theoretically in two recent papers [42,43]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations